The Appreciation of Ngloho Santri Society Towards Kubrosiswo Bintang Mudo Art in Ngloho Pringsurat Temanggung - Safitri, Setiorini Rahma; Utomo, Udi; Wadiyo, Wadiyo (Universitas Negeri Semarang, 2017)
People's appreciation of traditional art can be influenced by the views of the community. This study aims to examine the appreciation of Ngloho santri society towards Kubrosiswo Bintang Mudo Arts. This research uses qualitative method. The approach used is a contextual approach or how to understand a phenomenon by connecting it to other phenomena in a particular culture. In the context of this research, problem solving is placed within the socio-cultural context of Ngloho santri society.The appreciation of Ngloho santri society towards Kubrosiswo Bintang Mudo art splits into two, namely the young and the old group. Kubrosiswo Bintang Mudo since its inception in Ngloho Hamlet in 1989 was supported by a group of young people because of the desire to fulfill their aesthetic needs for a traditional art form that can represent their identity. This art for young people is understood as a symbol of trends, progress and modernity. The old group tends to keep a distance to this art. For them this art is considered jogedan art that is understood as the symbol of abangan art. In addition, the existence of pre-show and trance ritual sessions for the old group is considered to have come out of the Islamic faith.